International survey of investment adviser regulation - MacHarg, Marcia L.; Clark, Barton B. (Kluwer Law International, 1999)
Now in its second edition, International Survey of Investment Adviser Regulation is an unparalleled current guide to the regulatory systems in 29 jurisdictions. Each chapter represents the contribution of pre-eminent practitioners. A clear, uniform presentation permits easy comparisons among the different regulatory systems. International Survey of Investment Adviser Regulation allows investment advisers, regulators, lawyers and others in the investment management industry to evaluate the time, cost and legal considerations that will bear on strategic decisions to provide investment advisory services in specific countries. It also provides a guide for those engaged in the study of comparative regulatory systems as well as for policymakers who seek to improve and harmonize the regulation of investment advisers worldwide.